Changing the System from Within? The Role of Opposition Parties in Consolidating Democracy in Iraq Post-2019 - Alkhudary, Taif (My University, 2023)
This report examines the role that two of the most prominent opposition parties emerging out of the October 2019 protests – Al Bayt Al Watani and Imtidad – can play in consolidating democracy in Iraq. Findings indicate that both parties have developed strong identities based on unitary Iraqi nationalism and civic principles. Because of these identities, both continue to face a backlash from the dominant sectarian post-2003 parties. Both parties also face a lack of legal protections and substantial structural issues; both have struggled with developing common conventions of behaviour and ensuring that party conduct is carried out in accordance with democratic principles. Opposition parties also face pressures of exclusion from establishment parties, sometimes leading to violence, and compromising opposition parties’ autonomy and their ability to develop reformist policies and programmes.
Keywords: Peace Processes; Iraq